Evaluation of Parkinson's Disease Patients' Olfactory Dysfunction - Singh, Akhilesh Kumar; Krishana, Bal; Gupta, Meena (Highlights on Medicine and Medical Research Vol. 15, 2021)
Parkinson's disease (PD) is a neurodegenerative condition affecting dopaminergic neurons in the substantia nigra pars compacta. Along with motor disturbances, PD patients experience autonomic, cognitive, and sensory symptoms. Olfactory disturbances are important, but PD patients often overlook them. The current research included 30 Parkinson's disease patients and 30 age-matched controls aged 40 to 70 years. In addition to motor symptoms, a history of non-motor symptoms such as sleep disruptions, forgetfulness, constipation, and urinary problems was taken, despite the fact that these issues are also linked to ageing.18 patients said that they had a history of forgetfulness. Sleep disorders were present in 19 of the patients. Constipation was mentioned by 18 patients, and urinary problems were mentioned by 17 others. A history of olfactory deficiency or altered olfaction was also taken, as well as a change in taste sensation. 11 of the patients were conscious of their olfactory deficiency or changes. Two patients had complete bilateral anosmia, two patients had complete right sided anosmia, and five patients had a history of hyposmia among the 11 patients. There was no evidence of olfactory deficiency or altered olfaction in 21 of the patients.The taste sensations of 5 patients were also changed. The efficacy of putative preventive therapies hinges on the identification of earlier clinical markers. Other clinical markers in PD include upper limb kinematics activity, cognition impairment, depression, sleep disturbances, and micrographia, in addition to olfactory dysfunction. Preclinical detection will enable neuroprotective agents to be administered earlier in the disease process, so identifying subjects with an elevated risk of developing PD may aid in the development of neuroprotective treatment strategies.